Aspartyl-(asparaginyl) β-Hydroxylase, Hypoxia-Inducible Factor-1α and Notch Cross-Talk in Regulating Neuronal Motility. Issue 5 (2010) - Lawton, Margot; Tong, Ming; Gundogan, Fusun; Wands, Jack R.; de la Monte, Suzanne M.
Abstract : Aspartyl-(Asparaginyl)-β-Hydroxylase (AAH ) promotes cell motility by hydroxylating Notch. Insulin and insulin-like growth factor, type 1 (IGF-I) stimulate AAH through Erk MAP K and phosphoinositol-3-kinase-Akt (PI3K-Akt). However, hypoxia/oxidative stress may also regulate AAH . Hypoxia-inducible factor-1alpha (HIF-1α) regulates cell migration, signals through Notch, and is regulated by hypoxia/oxidative stress, insulin/IGF signaling and factor inhibiting HIF-1α (FIH) hydroxylation. To examine cross-talk between HIF-1α and AAH, we measured AAH, Notch-1, Jagged-1, FIH, HIF-1α, HIF-1β and the hairy and enhancer of split 1 (HE S-1) transcription factor expression and directional motility in primitive neuroectodermal tumor 2 (PNET2) human neuronal cells that were exposed to H2 O2 or transfected with short interfering RNA duplexes (siRNA) targeting AAH, Notch-1 or HIF-1α. We found that: (1) AAH, HIF-1α and neuronal migration were stimulated by H2O2; (2) si-HIF-1α reduced AAH expression and cell motility; (3) si-AAH inhibited Notch and cell migration, but not HIF-1α and (4) si-Notch-1 increased FIH and inhibited HIF-1α. These findings suggest that AAH and HIF-1α crosstalk within a hydroxylation-regulated signaling pathway that may be transiently driven by oxidative stress and chronically regulated by insulin/IGF signaling.